Beneficial Effects of Teucrium polium and Metformin on Diabetes-Induced Memory Impairments and Brain Tissue Oxidative Damage in Rats. (24th February 2015) - Mousavi, S. Mojtaba; Niazmand, Saeed; Hosseini, Mahmoud; Hassanzadeh, Zarha; Sadeghnia, Hamid Reza; Vafaee, Farzaneh; Keshavarzi, Zakieh
Abstract : Objective. The effects of hydroalcoholic extract of Teucrium polium and metformin on diabetes-induced memory impairment and brain tissues oxidative damage were investigated. Methods. The rats were divided into: (1) Control, (2) Diabetic, (3) Diabetic-Extract 100 (Dia-Ext 100), (4) Diabetic-Extract 200 (Dia-Ext 200), (5) Diabetic-Extract 400 (Dia-Ext 400), and (6) Diabetic-Metformin (Dia-Met). Groups 3–6 were treated by 100, 200, and 400 mg/kg of the extract or metformin, respectively, for 6 weeks (orally). Results . In passive avoidance test, the latency to enter the dark compartment in Diabetic group was lower than that of Control group (P < 0.01 ). In Dia-Ext 100, Dia-Ext 200, and Dia-Ext 400 and Metformin groups, the latencies were higher than those of Diabetic group (P < 0.01 ). Lipid peroxides levels (reported as malondialdehyde, MDA, concentration) in the brain of Diabetic group were higher than Control (P < 0.001 ). Treatment by all doses of the extract and metformin decreased the MDA concentration (P < 0.01 ). Conclusions. The results of present study showed that metformin and the hydroalcoholic extract of Teucrium polium prevent diabetes-induced memory deficits in rats. Protection against brain tissues oxidative damage might have a role in the beneficial effects of the extract and metformin.